A Maastrichtian terrestrial palaeoenvironment close to the K/Pg boundary in the Golfo San Jorge basin, Patagonia, Argentina. (January 2020) - Vallati, Patricia; De Sosa Tomas, Andrea; Casal, Gabriel
Abstract: In this paper, we present new palaeontological data regarding plant remains (palynomorphs, mesofossils, and leaves) from the uppermost part of the Lago Colhué Huapi Formation (Maastrichtian), at the headwaters of the Río Chico, Golfo San Jorge Basin. We also suggest a palaeoenvironmental reconstruction of these deposits, taking into account the information reported herein and previous palaeontological and sedimentological studies. Several spores of bryophytes, lycophytes, and monilophytes (ferns) as well as zygospores of Zygnemataceae form part of the freshwater aquatic ecosystem. The new species of Palmae affinity, Spinizonocolpites riochiquensis sp. nov. is described in this paper. Besides, we present the first record of leaf fragments with probable Palm-affinity in the Upper Cretaceous of Patagonia, which could reassert the presence of the Arecaceae in the basin. The palaeoflora recognized in the upper Lago Colhué Huapi Formation contributes to interpreting palaeoecological and palaeoclimatic conditions of a stratigraphic interval close to the Cretaceous/Paleogene extinction event, at the latitude of Patagonia. Highlights: Maastrichtian plant remains from the Golfo San Jorge Basin. A new species of Spinizonocolpites is described in the Lago Colhué Huapi Formation. Monocot fragmentary leaves are reported from the Maastrichtian of Patagonia. A reconstruction of a terrestrial environment close to the K/Pg boundary is proposed.